Reproductive performance of replacement heifers implanted as young calves or at weaning - L.R. Corah; A.R. Spell; D.L. Cook; M.D. Butine; K. Anderson; David M. Grieger (Kansas Agricultural Experiment Station Research Reports, 1997)
This study evaluated the effect of implanting potential replacement heifers (n=548) with Component E-C® (10 mg of estradiol and 100 mg of progesterone) between 45 and 120 days of age or at weaning (200 days of age) on future reproductive performance. Trials were conducted at five ranches in Kansas and one in Nebraska. At each location, heifers were allotted to three treatments: no implant (Control), one implant at 45 to 120 days of age (Early- IMP), or one implant at 2 00 days of age (Wean- IMP). No differences were detected among treatments for first service conception rate (55%), overall pregnancy rate (85%), or calving rate (80%). In addition, no differences were observed among treatments for pelvic area, reproductive tract score, or calving difficulty or for birth or weaning weights of their calves. We conclude that implanting replacement heifers with Component E-C early in life or at weaning had no effect on their subsequent reproductive performance.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Implant; Calves; Replacement heifers; Conception rate